Penerapan Metode Maut Dengan Pembobotan Entropy Dalam Sistem Pendukung Keputusan Penilaian Kinerja Guru Honor - Nola Dita Puspa; Mesran Mesran; Annisa Fadillah Siregar (Journal of Information System Research (JOSH), 2023)
The author examines the Smart Pure Vocational School, because the school has problems in assessing the performance of the best honorary teachers. Where the presence of a large number of teachers, of course, affects the speed of the assessment process and the accuracy in assessing the performance of the best honorary teachers. So the researchers created a decision support system that could assist the school in the process of evaluating honorary teacher performance. In a decision support system that is carried out using the MAUT method with Entropy weighting, where Entopy weighting is used to determine the criterion weight value of each predetermined criterion while the MAUT method is used to produce ranking results based on the alternatives and criteria that have been determined. So the results obtained from the decision support system that has been built using the MAUT calculation method with Entropy weighting, are very aimed at facilitating the Smart Pure Vocational School in the process of evaluating the performance of the best honorary teachers objectively, quickly and precisely. So as to produce results with a value of 0.9611 from alternative A12 on behalf of Siti Maimunah.